Recombinant shingles vaccination and the risk of cardiovascular events - Fabiana Corsi-Zuelli; Fang Li; Rachel Upthegrove; John A. Todd; Betty Raman; Paul J. Harrison; Maxime Taquet (Nature Medicine, 2026)
Abstract The recombinant herpes zoster (shingles) vaccine may reduce risks of cardiovascular disease. However, existing studies have compared vaccine recipients with non-recipients and, thus, are susceptible to confounding. To mitigate these biases, we conducted a natural experiment created by the rapid transition from the live attenuated to the recombinant shingles vaccine in the United States. We compared incidences of a composite cardiovascular endpoint (ischemic heart disease, heart failure or ischemic stroke) among adults aged ≥60 years vaccinated immediately before versus immediately after this transition. The recombinant vaccine was associated with a 9% decrease in cardiovascular burden over 7 years (restricted mean time lost (RMTL) ratio = 0.91, 95% confidence interval (CI): 0.88−0.95). The association attenuated over time and was significant for ischemic heart disease (10% decrease in burden; RMTL ratio = 0.90, 95% CI: 0.87−0.94) and heart failure (12% decrease in burden; RMTL ratio = 0.88, 95% CI: 0.83−0.93) in both sexes and ischemic stroke in males (12% decrease; RMTL ratio = 0.88, 95% CI: 0.78−0.98). An association was also seen for atrial fibrillation (7% decrease in burden; RMTL = 0.93, 95% CI: 0.88−0.98) but not other cardiac, peripheral and cerebrovascular outcomes. Results were consistent in secondary analyses. These results justify clinical trials and mechanistic studies to investigate potential cardioprotective effects of shingles vaccines.